Highly Efficient Semi-Continuous Extraction and In-Line Purification of High β-O-4 Butanosolv Lignin - Zijlstra, Douwe Sjirk; de Korte, Joren; de Vries, Ernst P. C.; Hameleers, Lisanne; Wilbers, Erwin; Jurak, Edita; Deuss, Peter Joseph (Frontiers in Chemistry, 2021)
Innovative biomass fractionation is of major importance for economically competitive biorefineries. Lignin is currently severely underutilized due to the use of high severity fractionation methodologies that yield complex condensed lignin structure that limits high-value applicability. Mild lignin fractionation conditions can lead to lignin with a more regular C-O bonded structure that has increased potential for higher value applications. Nevertheless, such extraction methodologies typically suffer from inadequate lignin extraction efficiencies and yield. (Semi-)continuous flow extractions are a promising method to achieve improved extraction efficiency of such C-O linked lignin. Here we show that optimized organosolv extraction in a flow-through setup resulted in 93-96% delignification of 40 g walnut shells (40 wt% lignin content) by applying mild organosolv extraction conditions with a 2 g/min flowrate of a 9:1 n-butanol/water mixture with 0.18 M H2SO4 at 120 °C in 2.5 hours. 85 wt% of the lignin (corrected for alcohol incorporation, moisture content and carbohydrate impurities) was isolated as a powder with a high retention of the β-aryl ether (β-O-4) content of 63 linking motifs per 100 C9 units. Close examination of the isolated lignin showed that the main carbohydrate contamination in the recovered lignin was butyl-xyloside and other butoxylate carbohydrates. The work-up and purification procedure were investigated and improved by the implementation of a caustic soda treatment step and phase separation with a continuous integrated mixer/separator (CINC). This led to a combined 75 wt% yield of the lignin in 3 separate fractions with 3% carbohydrate impurities and a very high β-O-4 content of 67 linking motifs per 100 C9 units. Analysis of all the mass flows showed that 98% of the carbohydrate content was removed with the inline purification step, which is a significant improvement to the 88% carbohydrate removal for the traditional lignin precipitation work-up procedure. Overall we show a convenient method for inline extraction and purification to obtain high β-O-4 butanosolv lignin in excellent yields.